A comparison of the acute-phase response in middle aged and elderly patients. Issue 759 (January 1989) - Woo, J.; Arumanayagam, M.; MacDonald, D.; Woo, K. S.
Abstract : The acute phase response in middle aged and elderly patients was compared by measuring the ratio of the peak C-reactive protein to peak creatine kinase level during the three day period after acute myocardial infarction. No difference in ratio was observed between a middle aged group of 14 patients (10.2 +/- 4.0 mean +/- s.e.), and an elderly group of 13 patients (9.1 +/- 1.5). C-reactive protein levels in two groups of middle aged and elderly control patients were similar (10.1 +/- 0.04 mg/l and 11.8 +/- 0.10 mg/l respectively). Production of C-reactive protein does not appear to be impaired in the elderly.